“Memory, Aging and the Brain” – Uma homenagem a Lars-Göran Nilsson - Benetti, Idonezia Collodel (Revista de Psicologia da IMED, 2014)
This recension aims at presenting the book “Memory, aging and the brain” – a festschrift in honour of Lars-Göran Nilsson”, not yet translated into the Brazilian Portuguese.  Comprising 16 articles, organized and edited by Lars Bäckman and Lars Nyberg, it is anchored on studies focused on the brain related functions, with which these two scholars pay a tribute to Lars-Göran Nilsson, for the benefits he had provided to the academic world and to the society in general with the studies surrounding the brain related to aging studies, related to the genetic influence on memory and to the leisure-time activities in old age as predictors of impending dementia.